Environmental impact of amino acids on the release of selenate immobilized in hydrotalcite: Integrated interpretation of experimental and density-functional theory study. (July 2021) - Wang, Mengmeng; Akamatsu, Hirofumi; Dabo, Ismaila; Sasaki, Keiko
Abstract: The environmental impact of amino acids on the release of SeO4 2− immobilized into hydrotalcite (Mg2 Al-LDH) which belongs to the layered double hydroxides (LDHs) family was investigated by experimental study and the observed layer structure of hydrotalcite was verified through density-functional theory (DFT) calculations. Glycine, l -cysteine, and l -aspartic acid, which have smaller molecular sizes, can release SeO4 2− largely due to intercalation, unstabilization of Mg2 Al-LDH and simple dissolution, while l -tryptophan and l -phenylalanine caused limited SeO4 2− release due to their larger sizes and aromaticity. XRD patterns for the solid residues after intercalation of amino acids revealed that the layer distance of Mg2 Al-LDH was partially expanded. The main peaks and shoulder features corresponding to d 003 diffraction were well explained by DFT simulations using glycine as a model: the layer spacing of the main peak is responsible for the remaining SeO4 2− and singly stacked glycine molecule and the layer spacing of the shoulder peak was well explained by doubly stacked glycine molecules. Hydrogen bonds between amino acids and hydroxyl ions in the metallic layers of Mg2 Al-LDH were responsible for the stable configuration of the intercalated Mg2 Al-LDH. This study indicates potential limitations to the stability of low-level radioactive wastes of 79 Se in repositories which are affected by smaller molecules of amino acids released through degradation of organic matters in the pedosphere. Graphical abstract: Image 1 Highlights: Effect of amino acids on the mobility of selenate in LDH was explored. Smaller sizes of amino acids promoted the release of selenate from LDH. DFT predicted the interlayer spaces of LDH after intercalation of amino acids. Singly stacked configuration of glycine was the most stable in LDH. Cysteine suppressed the Mg dissolution from LDH.